A modern approach to evaluating the effectiveness of the respiratory rehabilitation program for patients after a new coronavirus infection COVID-19 - V. V. Afanasyeva; A. A. Potapchuk (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2023)
The objective was to evaluate the effectiveness of the respiratory rehabilitation program for patients after a new coronavirus infection COVID-19 from the standpoint of the International Classification of Functioning, Disability and Health.Methods and materials. A study of 59 patients who underwent a new coronavirus infection COVID-19 and were hospitalized after 2–3 months for a rehabilitation course was conducted on the basis of the Pavlov University in 2020–2022. The main group included 38 patients (12 men and 26 women), the comparison group consisted of 21 patients (14 men and 7 women). The program of respiratory rehabilitation of patients who underwent COVD-19 included therapeutic gymnastics (breathing exercises, restorative physical exercises, special strength-oriented physical exercises), Nordic walking and physiotherapy procedures. The program developed by us was implemented during 2 weeks of inpatient stay of patients. Evaluation of the effectiveness of the respiratory rehabilitation program for patients who underwent COVID-19 was carried out on the basis of GOST R 57960 – 2017 “Evaluation of the results of rehabilitation services”.Results. Based on the evaluation of the effectiveness of rehabilitation in both groups according to GOST R 57960 – 2017 “Evaluation of the results of rehabilitation services”, the sum of individual indicators in patients of the main group was 84.7 points, the average score was 2.2. The sum of individual indicators in patients of the comparison group was 25.4 points, the average score was 1.2. Thus, the effectiveness of respiratory rehabilitation of patients of the main group according to GOST – excellent, in patients of the comparison group – satisfactory.Conclusions. The ICF categories have been formed, which allow us to provide objective information about the condition of patients who have undergone a new coronavirus infection in moderate and severe forms. A program of respiratory rehabilitation has been developed, including classes in breathing exercises, restorative physical exercises, special strength-oriented physical exercises, Nordic walking, and physiotherapy procedures. The effectiveness of respiratory rehabilitation of patients of the main group can be recognized as excellent.